Back Cover: Mix to Validate: A Facile, Reversible PEGylation for Fast Screening of Potential Therapeutic Proteins In Vivo (Angew. Chem. Int. Ed. 27/2013). Issue 27 (6th June 2013) - Kim, Tae Hyung; Swierczewska, Magdalena; Oh, Yumin; Kim, AeRyon; Jo, Dong Gyu; Park, Jae Hyung; Byun, Youngro; Sadegh‐Nasseri, Scheherazade; Pomper, Martin G.; Lee, Kang Choon; Lee, Seulki
<x xml:space="preserve">Abstract</x> Increasing the half‐life of therapeutic proteins in a specific, fast, and reliable way could greatly benefit the discovery of novel protein drugs. In their Communication on page 6880 ff., K. C. Lee, S. Lee, and co‐workers conjugate Ni‐NTA to poly(ethylene glycol) and then label oligohistidine‐tagged therapeutic proteins to improve their stability in vivo without compromising bioactivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>